The Utilization of Microbial Inoculants Based on Irradiated Compost in Dryland Remediation to Increase the Growth of King Grass and Maize - T.R.D. Larasati; N. Mulyana; D. Sudradjat (PPIKSN-BATAN, 2016)
This research was conducted to evaluate the capability of functional microbial inoculants to remediate drylands. The microbial inoculants used consist of hydrocarbon-degrading microbial inoculants and plant-growth-promoting microbial inoculants. Compost-based carrier was sterilized by a gamma irradiation dose of 25 kGy to prepare seed inoculants. The irradiated-compost-based hydrocarbon-degrading microbial inoculants and king grass (Pennisetum purpureum Schumach.) were used to remediate oil-sludge-contaminated soil using in-situ composting for 60 days. The results showed that they could reduce THP (total petroleum hydrocarbons) by up to 82.23%. Plant-growth-promoting microbial inoculants were able to increase the dry weight of king grass from 47.39 to 100.66 g/plant, N uptake from 415.53 to 913.67 mg/plant, and P uptake from 76.52 to 178.33 mg/plant. Cow dung and irradiated-compost-based plant-growth-promoting microbial inoculants were able to increase the dry weight of maize (Zea mays L.) from 5.75 to 6.63 ton/ha (12.54%) and dry weight of grain potential from 5.30 to 7.15 ton/ha (35.03%). The results indicate that irradiated-compost-based microbial inoculants are suitable for remediating a dryland and therefore increase potential resources and improve the quality of the environment.Received: 17 March 2015; Revised: 28 October 2015; Accepted: 28 October 2015